Gawe Rafah Tradition as Interreligious Conflict Resolution in West Lombok Regency - Anam, Fikri Khairul; Wiranata, Satria (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Humans identify as religious followers and cultural successors. Indonesia's religious and cultural diversity has frequently become the source of conflict. Traditional law is frequently chosen as an independent law because existing legal values are enforced and upheld by the community as well as bodies or institutions in the area. The goal of this research is to understand the interreligious and cultural approach known as Gawe Rafah. A Sasak communal custom that serves as a platform for interreligious and cultural counseling. This was also employed in Mareje Village, West Lombok Regency, to settle disputes between Muslims and Buddhists. This study used qualitative research to critically characterize a social interaction in society in order to seek and find meaning in its genuine environment (natural setting). The case study approach is an activity that involves gathering data and information in depth. This means that the primary data for this study came from interviews done by researchers with religious and traditional leaders at the Gawe Rafah event. Researchers likewise used secondary data, such as information from journals, books, and articles. In this tradition, there are findings about the cultural spirit called Iqrar Sopoq Tundun (one descendant), where people try to unite with ethnic and cultural similarities as Sasak Lombok people. This pattern shows that traditional communities can override their religion, personal will and even government rules, In order to reach a consensus that allows them to coexist in harmony and peace. This research is expected to open the insights of the people in conflict areas that based on open communication between communities, ancestral practices like this can become unique and wisdom in each region in Indonesia.